Preferential orientation of diamond formation on TaC: Diamond(111)//TaC(111) - Shaohua Lu; Xiongtao Zhang; Yuhao Zheng; Meiyan Jiang; Chengke Chen; Xiaojun Hu (Functional Diamond, 2024)
Experimental results showed that for the diamond film prepared by hot filament chemical vapor deposition (HFCVD) using Ta filament, TaC existed between diamond and the silicon substrate, and diamond grew directly on TaC, while the inherent mechanism was not clear. Here, a special coherent interface Diamond(111)//TaC(111) is observed using high resolution transmission electron microscopy, and then we explore the effects of the TaC with different lattice planes on the diamond formation by first-principle calculations. The results show that C tends to adsorb on the TaC(111) C-terminated surface. The strong covalent bond between C from diamond and Ta from TaC is formed in the Diamond(111)//TaC(111) interface, while only C–C covalent bonds are formed at the Graphite(002)/TaC(111). This makes diamond thermodynamically more stable than graphite on the TaC surfaces. Our investigations provide critical information to understand the complex diamond formation mechanism, especially with the presence of TaC.